Rational Force of Analogy/Qiyās in Law: Logic of Law in Islamic and Contemporary Legal Reasoning - Komath, Muhammed (Informal Logic, 2025)
Analogy is an inherently fragile form of argument, as it derives the conclusion from similarity, while overlooking dissimilarities. Yet law fundamentally depends upon analogical reasoning to ensure consistency and predictability in its rulings. This entanglement of fragility and necessity compels the legal traditions, both Islamic and contemporary, to articulate a theory of legitimacy that justifies analogy when applied in law. The most successful explanation among different considerations, I argue, is the one that is anchored in logic. This logical grounding is a shared feature among contemporary legal theorist Scott Brewer, the informal logician Douglas Walton, and the 12th-century Muslim jurist-logician al-Ghazzālī, as all three insist that the justification of legal analogy is logical. This paper aims to trace the thematic contours of these logical frameworks in order to demonstrate, drawing primarily on al-Ghazzālī’s two works: al-Mustaṣfā fī Uṣūl al-Fiqh and al-Muntaḥal fī al-Jadal, that al-Ghazālī’s model of analogical reasoning effectively integrates key elements of Brewer’s abduction model and Walton’s model of defeasible argument.